Computer Applications in Engineering and Management. - Berwal, Parveen; Dhatterwal, Jagjit Singh; Kaswan, Kuldeep Singh; Kant, Shashi ([Place of publication not identified] : Chapman and Hall/CRC, 2022)
The book Computer Applications in Engineering and Management is about computer applications in Management, Electrical Engineering, Electronics Engineering and Civil Engineering. It covers the software tools for office automation, introduces the basic concepts of database management, and provides an overview about the concepts of data communication, internet, and e-commerce. Additionally, the book explains the principles of computing management used in construction of buildings in Civil Engineering and the role of computers in power grid automation in Electronics Engineering. Features: Provides an insight to prospective research and application areas related to industry and technology Includes industry-based inputs Provides a hands-on approach for readers of the book to practice and assimilate learning This book is primarily aimed at undergraduates and graduates in computer science, information technology, civil engineering, electronics and electrical engineering, management, academicians, and research scholars.
1. Introduction of Management, Civil, Electrical and Electronic (MCEE) in Computers.2 Management Cost computing. 3. Management Rule Mining computing. 4. Quality Learning management computing.5. MAS based data modeling in civil Engineering. 6. Automated Building Information System in civil.7. Infrastructure monitoring and sustainable building and construction in civil. 8. Circuit Simulation and Design.9. Computational Electromagnetics. 10. Mathematical and Computational Methods.11. Basic Chipper design in electronic computing.12. Demographic and principles of electronic computing. 13. Rehabilitation computing in electronic computing.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering -- Data processing; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General